2021
DOI: 10.1002/aesr.202100004
|View full text |Cite
|
Sign up to set email alerts
|

Operando Characterization Techniques for All‐Solid‐State Lithium‐Ion Batteries

Abstract: Lithium‐ion batteries (LIBs), which utilize a liquid electrolyte, have established prominence among energy storage devices by offering unparalleled energy and power densities coupled with reliable electrochemical behavior. The development of solid‐state batteries (SSBs), utilizing a solid electrolyte layer for ionic conduction between the electrodes, could potentially offer further performance improvements in key areas such as energy density and safety. However, to date, SSBs remain unable to match the perform… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
44
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 47 publications
(45 citation statements)
references
References 133 publications
(196 reference statements)
1
44
0
Order By: Relevance
“…In situ differential electrochemical mass spectrometry (DEMS) measurements were performed to further evaluate the effectiveness of the coating in suppressing outgassing reactions. [52] In recent years, it has been shown that certain coating chemistries are capable of reducing the evolution of gaseous degradation products that are detrimental to the battery operation. [41,52] The DEMS results for the different NCM85 CAMs are shown in Figure 6 and Figures S25-S28 (Supporting Information).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In situ differential electrochemical mass spectrometry (DEMS) measurements were performed to further evaluate the effectiveness of the coating in suppressing outgassing reactions. [52] In recent years, it has been shown that certain coating chemistries are capable of reducing the evolution of gaseous degradation products that are detrimental to the battery operation. [41,52] The DEMS results for the different NCM85 CAMs are shown in Figure 6 and Figures S25-S28 (Supporting Information).…”
Section: Resultsmentioning
confidence: 99%
“…[52] In recent years, it has been shown that certain coating chemistries are capable of reducing the evolution of gaseous degradation products that are detrimental to the battery operation. [41,52] The DEMS results for the different NCM85 CAMs are shown in Figure 6 and Figures S25-S28 (Supporting Information). Four different gases were detected, H 2 , O 2 , CO 2 , and SO 2 .…”
Section: Resultsmentioning
confidence: 99%
“…[1][2][3] Lithium thiophosphates, which exhibit the highest roomtemperature ionic conductivities [4] among the reported superionic solid electrolytes (SEs) along with favorable mechanical properties, have been shown to be unstable when in contact with energy-dense cathode active materials (CAMs), such as LiNi x Co y Mn z O 2 (referred to as NCM), especially at the high voltages they are usually operated at. [5][6][7][8][9][10][11] Therefore, it is imperative to introduce a buffer layer between CAM and SE. In the past, various protective CAM coatings prepared by different techniques have been reported.…”
Section: Introductionmentioning
confidence: 99%
“…Engineering of stable interfaces is one of the major challenges on the route to bulk‐type solid‐state batteries (SSBs) that are capable of competing with liquid electrolyte‐based Li‐ion batteries (LIBs) in terms of electrochemical performance [1–3] . Lithium thiophosphates, which exhibit the highest room‐temperature ionic conductivities [4] among the reported superionic solid electrolytes (SEs) along with favorable mechanical properties, have been shown to be unstable when in contact with energy‐dense cathode active materials (CAMs), such as LiNi x Co y Mn z O 2 (referred to as NCM), especially at the high voltages they are usually operated at [5–11] . Therefore, it is imperative to introduce a buffer layer between CAM and SE.…”
Section: Introductionmentioning
confidence: 99%
“…A deeper understanding of the battery-cycle process in ASSBs, i.e., the formation of dendrites, phase evolution, and deterioration of the interface, can help identify a possible solution to battery degradation. In situ / operando techniques provide the roadmap to draw the mechanism of ion transport in ASSBs. Postmortem analyses of cell components though provide the products formed during the electrochemical process, and the information provides a very narrow view of the real cycle operation. On the other hand, in situ data acquisition during cell cycles coupled with various other analytical techniques, i.e., in operando route, provides real-time process status.…”
Section: Introductionmentioning
confidence: 99%